The Physical Architecture Relevance in Designing Virtual Environment - Hui, Gavin Tio Kang (MAJ - Malaysia Architectural Journal, 2025)
The integration of digital reality systems in building design has been the way forward over the past half-century. The paper analyses the impacts of rising demand for digital environments in the architecture industry and the relevance of an architect in designing virtual environments (VEs). As there are numerous architectural design considerations, the physical architecture relevance is streamlined into three components, namely relevance in human lifestyle changes, relevance in sense of touch and relevance in scale. Likert-scale survey questionnaire collects data to evaluate the implications of different physical spatial qualities on the user’s satisfaction, perception, and cognition. Architect is relevant in addressing the design limitations and fostering collective multidisciplinary synergy in the effort of establishing a positive impact for VEs. Semi-structured interviews are carried out to examine the different relationships between physical spatial layout and VEs. By optimising the functional, spatial, ergonomic, sensuous, economic, and technological relationships, an architect’s expertise is fundamental for an immersive mixed-reality experience. Content analysis is conducted to synthesize the future roles of an architect. Architect is relevant in formulating a holistic design strategy from the environmental, social and governance aspects. The evolving roles of an architect are synthesized based on the Architects (Scale of Minimum Fees) Rules 2010. Digital transformation is momentous and adaptation strategy is the way forward. The demand for an architect will not become redundant, but it will evolve alongside the context of VE. Human-centric VE with XR technology-infused activities is the key to digitalising the built environment.